IMPLEMENTATION OF THE INDIRECT DEFINITION IN THE RUSSIAN-UZBEK PHRASEOLOGICAL DICTIONARY - Баратова Ситора Рашидовна (Bright Mind Publishing, 2025)
The article is devoted to the indirect definition, which belongs to the type of extended definitions and is quite often found in the Russian-Uzbek phraseological dictionary. Indirect description serves to indicate a typical situation in which a phraseological unit of the source language is used or to clarify the semantic content of which a wide context is required, representing a certain etymological reference.
Keywords: Bilingual phraseography, indirect definition, situational, dictionary article, phraseological meaning.